PRINCIPLES AND MECHANISMS FOR ASSESSING AND FORECASTING CRISES IN THE CONTEXT OF DIGITALIZATION - Trofimov, Vladimirovich; Ludushkina, Elena; Kornilova, Elena; Kislinskaya, Marina; Frolov , Vladislav; Popova, Yulia (Revista Inclusiones, 2020)
The authors study the existing principles and mechanisms for assessing and forecasting crises, as well as determine the possibility of using them in the context of digital transformation. The following research methods are used in the work: empirical, theoretical and quantitative. Within the framework of the study, the authors explore the literary sources on the issue, in particular, works that examine assessment and forecasting principles and works on crisis management and the influence of Industry 4.0 on the current changes in the world. The authors study the general management mechanism and justify the possibility for using the mechanism at organizational, regional, national and global levels. The most common approaches to crisis forecasting are explored. The authors provide the calculation wherein the crisis forecasting mechanism is applied using the example of the Russian Federation. The crisis state index is developed and its applicability for identifying pre-crisis and crisis states is proven. The novelty of the study consists in the fact that the universal model for assessing the crisis state based on economic indicators is developed.